Histórias de vida de professoras negras : trajetórias de sucesso - Nascimento, Cleonice Ferreira do (2012)
This paper analyzes the life trajectories of black teachers of basic education, specifically those who teach in the early years of elementary school in the town of Várzea Grande / MT. The present study aimed to understand the possible influence of race / color in the trajectories and how teachers meet specific goals the paths of life - academic and vocational - from black teachers, verifying what motivated the choice of teaching; 'contributions to family choosing the teaching profession and know the network of relationships established by the teachers and who have helped in the study and profession. The survey was conducted from a qualitative approach. For data collection, we used the methodology of oral history, with the technical history of life. Accordingly, we used the interview to consider it more appropriate to capture the life experiences of black teachers, social subjects in this study. Almost all teachers interviewed are from working class families. In the course of study to a successful school, completing the basic education and higher education because of the important emotional support, moral, psychological and economic family. As regards the life of the interviewees, one sees the influence of race / color in some teaching careers. It was found that there is an idea or belief that black teachers have no power and intellectual capacity to assume leadership positions in the school environment. To stay in the power conquered and overcome these hurdles race, the teachers used the strategy to demonstrate and prove that they had the field of professional knowledge. The inequalities between whites and blacks in Brazil, based on the phenotype of the population. The lighter pigmentation of the skin of a person, the more opportunities to assume positions of high status and wages, and the darker the skin tone, the less likely to take ownership of jobs for social prestige. In other words, the color / race can determine the position, status and place of people in society. This is because racism is one of the pillars that structure social relations in this country, including in education.